The development, implementation and evaluation of interventions to reduce workplace sitting: a qualitative systematic review and evidence-based operational framework - Kelly Mackenzie; Elizabeth Such; Paul Norman; Elizabeth Goyder (BMC, 2018)
Abstract Background Prolonged sitting is associated with increased risks of cardiovascular disease, Type 2 diabetes, some cancers, musculoskeletal disorders and premature mortality. Workplaces contribute to a large proportion of daily sitting time, particularly among office-based workers. Interventions to reduce workplace sitting therefore represent important public health initiatives. Previous systematic reviews suggest such interventions can be effective but have reported wide variations. Further, there is uncertainty as to whether effectiveness in controlled trials can be replicated when implemented outside the research setting. The aims of this review are to identify factors important for the implementation of workplace sitting interventions and to translate these findings into a useful operational framework to support the future implementation of such interventions. Methods A qualitative systematic review was conducted. Four health and social science databases were searched for studies set in the workplace, with office-based employees and with the primary aim of reducing workplace sitting. Extracted data were primarily from author descriptions of interventions and their implementation. Inductive thematic analysis and synthesis was undertaken. Results Forty studies met the inclusion criteria. Nine descriptive themes were identified from which emerged three higher-order analytical themes, which related to the development, implementation and evaluation of workplace sitting interventions. Key findings included: the importance of grounding interventions in theory; utilising participative approaches during intervention development and implementation; and conducting comprehensive process and outcome evaluations. There was a general under-reporting of information relating to the context within which workplace sitting interventions were implemented, such as details of local organisation processes and structures, as well as the wider political and economic landscape, which if present would aid the translation of knowledge into "real-world" settings. Conclusions These findings provided the basis for an operational framework, which is a representation of all nine descriptive themes and three higher-order analytical themes, to support workplace sitting intervention development, implementation and evaluation. Once tested and refined, this framework has the potential to be incorporated into a practical toolkit, which could be used by a range of organisations to develop, implement and evaluate their own interventions to reduce workplace sitting time amongst staff.